Vincetoxicum strigosum (Asclepiadoideae, Apocynaceae), a new species from northeastern Thailand - Kidyoo, Aroonrat (Phytotaxa, 2020)
A new slender twining herb, Vincetoxicum strigosum A. Kidyoo, from northeastern Thailand is described and illustrated. This species is morphologically similar to V. kerrii (Craib) A. Kidyoo, but can be distinguished by several morphological, anatomical, and ultrastructural characters, i.e. leaf indumentum, inflorescence architecture, shape and size of calyx lobes, stipe of gynostegium, apex of corona lobes, and shape of corpusculum.